(untitled) (Experimental biology, 2018)
miRNAs demonstrate a class of small, non-coding RNAs that can regulate the expression of genes, and are associated with approximately all known physiological and pathological processes, especially cancer. Expression of many genes is regulated by binding of miRNA with mRNA, therefore it is required to identify candidate genes of esophageal and stomach cancers and to what extent they can interact with miRNA. To determine the important miRNAs biding sites in genes, involved in the development of esophageal and stomach cancers, there were used the MirTarget program. The article presents the results of studying the characteristics of the interaction of miRNAs with mRNAs of 121 genes involved in the development of esophageal and stomach cancer. From the 68 candidate genes, participating in the development of esophageal cancer, only 54 genes were targets for miRNAs. 148 miRNAs have binding sites at 5’UTR, CDS, and 3’UTR, and the average free binding energy (ΔG) of miRNAs with mRNAs was -126 kJ/mole, -121 kJ/mole and -111kJ/mole, respectively. 20 miRNAs and mRNA genes associations with a free energy of interaction more than -125 kJ/mole are recommended for the diagnosis of esophageal cancer. From the 106 candidate genes, participating in the development of stomach cancer, 86 genes were targets for miRNAs. 253 miRNAs have binding sites at 5’UTR, CDS and 3’UTR and the average free binding energy (ΔG) of miRNAs with mRNAs was -124 kJ/mole, -116 kJ/mole and -110 kJ/mole, respectively. 28 miRNAs associations with mRNAs are recommended for the diagnosis of stomach cancer that have a free energy of interaction more than -125 kJ/mole. The mRNAs of most genes containing two or more miRNA binding sites with overlapping of their nucleotide sequences form clusters. Based on the obtained results, groups of miRNA and mRNA associations of candidate genes are recommended to develop methods for early diagnosis of esophageal and stomach cancer. The 768 previously unreported binding sites for 3071 miRNAs, which may be the main ones in the regulation of genes responsible for the development of esophageal and stomach cancers was established. Key words: mRNA, miRNA, genes, oncological diseases, esophageal cancer, stomach cancer.